CODE MIXING IN ESL CLASSROOM: BARRIER OR BRIDGE TO LANGUAGE LEARNING? - Islamia, Ismi; Giri Aditama, Madya; Ainun Najib, Reza (Melekliterasi Press, 2025)
This article explores the dual role of code mixing in English as a Second Language (ESL) classrooms, examining whether it serves as a barrier or a bridge to effective language learning. Drawing from theoretical perspectives and practical classroom observations, the discussion highlights the potential benefits of code-mixing, such as enhancing comprehension, reducing learner anxiety, and facilitating smoother transitions to target language use. However, the article also addresses the potential drawbacks, including reduced exposure to English, overreliance on the first language (L1), and limited immersion. The findings suggest that code-mixing can be a valuable pedagogical tool when used strategically and in moderation. Ultimately, the article concludes that the impact of code mixing depends on how it is implemented by educators, emphasizing the importance of thoughtful and purposeful application to maximize its benefits while minimizing its risks in ESL settings. Therefore, ESL educators must exercise pedagogical awareness to balance innovation and integrity in language teaching while adapting to learners’ linguistic needs.